Combined delivery of FGF‐2, TGF‐β1, and adipose‐derived stem cells from an engineered periosteum to a critical‐sized mouse femur defect. Issue 3 (23rd December 2016) - Romero, Raimundo; Travers, John K.; Asbury, Emilie; Pennybaker, Attie; Chubb, Laura; Rose, Ruth; Ehrhart, Nicole P.; Kipper, Matt J.
Abstract: Critical‐sized long bone defects suffer from complications including impaired healing and non‐union due to substandard healing and integration of devitalized bone allograft. Removal of the periosteum contributes to the limited healing of bone allografts. Restoring a periosteum on bone allografts may provide improved allograft healing and integration. This article reports a polysaccharide‐based tissue engineered periosteum that delivers basic fibroblast growth factor (FGF‐2), transforming growth factor‐β1 (TGF‐β1), and adipose‐derived mesenchymal stem cells (ASCs) to a critical‐sized mouse femur defect. The tissue engineered periosteum was evaluated for improving bone allograft healing and incorporation by locally delivering FGF‐2, TGF‐β1, and supporting ASCs transplantation. ASCs were successfully delivered and longitudinally tracked at the defect site for at least 7 days post operation with delivered FGF‐2 and TGF‐β1 showing a mitogenic effect on the ASCs. At 6 weeks post implantation, data showed a non‐significant increase in normalized bone callus volume. However, union ratio analysis showed a significant inhibition in allograft incorporation, confirmed by histological analysis, due to loosening of the nanofiber coating from the allograft surface. Ultimately, this investigation shows our tissue engineered periosteum can deliver FGF‐2, TGF‐β1, and ASCs to a mouse critical‐sized femur defect and further optimization may yield improved bone allograft healing. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 900–911, 2017.